Potencial da regeneração natural em área antropizada e conduzida com diferentes práticas de restauração, no sul do bioma Mata Atlântica - Andrade, Juliane dos Santos (2021)
Degraded or altered areas have been the focus of restoration practices, with the aim of restoring the ecosystem in a similar way to the natural one. Active restore practices generally allow recovery to take place faster. Thus, the aim of this study was to characterize the natural regeneration potential of tree and shrub species under different restoration practices, considering active restoration, represented by pure planting (Pp) with four native species and mixed planting (Pm), with different arrangement of species. These environments provided different levels of shading and were compared with the area undergoing passive restoration, after isolation in a heavily anthropized area in the extreme south of the Atlantic Forest biome, Brazil. Three sampling units (UA) (1 m x 2 m) were allocated in each of the 16 plots in Pm and 12 in Pp, totaling 84 UAs, 8% and 6% of the area of Pm and Pp, respectively. At the same time, another 24 UAs were installed around the areas, to characterize the original condition, after isolation of the area (AResP - control), totaling 108 UAs. The regenerating individuals were categorized into three height classes (Cl-I= 20 – 50 cm; Cl-II= 50.1 – 100 cm; Cl-III= >100cm – DBH< 1cm). Natural regeneration in areas undergoing passive and active restoration was characterized in terms of floristic composition, richness, diversity, evenness, similarity, distribution of individuals in size classes, mode of fruit dispersion and successional group of species. The environmental variables temperature and humidity of air and soil, light intensity (IL), in addition to richness, diversity and evenness, were subjected to Principal Component Analysis (PCA), also obtaining clusters of similar areas. The present regeneration is associated with the effect of silvicultural interventions carried out in the study area with low soil quality, the use of Brachiaria sp. in the portion of the area with subsequent use with Pp, and the time after intervention by isolation of the area and plantations. PCA indicated the influence of environmental variables, such as IL, soil temperature in autumn, air temperature in spring and summer, as indicators of areas with passive restoration – AResP and with pure planting with Casearia sylvestris. The AResP, in an isolated condition for about 10 years, remained with low resilience, despite its adjacency to a remnant of Seasonal Deciduous Forest. Areas six years after Pp with Inga vera and Schinus terebinthifolius showed greater richness, diversity and evenness, followed by areas with four years old, used with Pm. The predominance of species with biotic dispersion, belonging to the three successional groups (pioneer, secondary and climax) indicates that the coverage favored the entry and establishment of natural regeneration. We conclude that the initial natural regeneration can be favored by shading equal to or greater than 30%, in an environment with strongly anthropized soil. Regardless of the type of silvicultural practice, using pure planting in small plots and/or species interspersed in mixed planting, the environment presented conditions that were factorable to the entry and establishment of new species.